Nature variations of OsNLP4 responsible for nitrogen use efficiency divergence in the two rice subspecies - Jie Wu; Ying Song; Guangyu Wan; Liangqi Sun; Jingxian Wang; Hongkai Wu; Shimei Wang; Chuanzao Mao; Peng Qin; Shigui Li; Chengcai Chu; Chengbin Xiang (Nature Communications)
Abstract Nitrogen use efficiency (NUE), a critical determinant of crop productivity and agricultural sustainability, varies significantly between indica and japonica subspecies. Here, we identify three coding-region SNPs in OsNLP4 underlying this divergence. These SNPs enhance the binding affinity of OsNLP4 indica to nitrate response elements (NREs), amplifying transcriptional activation of nitrogen metabolism and iron homeostasis genes. Introgression of the OsNLP4 indica allele into elite japonica cultivar XS134 increases both grain yield and NUE by 12–25% across multi-location field trials under varying nitrogen regimes. Heterologous expression in Arabidopsis increases shoot biomass by 23%, demonstrating possible conservation of function in dicots. Mechanistically, the indica allele’s stronger NRE-binding capacity synergistically modulates downstream pathways. Furthermore, combining OsNLP4 indica with balanced nitrogen-iron fertilization boosts NUE by 30–32%. Our findings resolve a critical genetic basis of indica-japonica NUE divergence, provide a validated strategy for improving yield and NUE of commercial japonica varieties, and highlight OsNLP4 indica as a cross-species genetic resource for sustainable agriculture.